Ethnic group differences in racial identity attitudes, perceived discrimination and mental health outcomes in African American, Black Caribbean and Latino Caribbean college students. Issue 1 (2nd January 2016) - Sanchez, Delida; Awad, Germine H.
Abstract : The increasing presence of Black Caribbean and Latino Caribbean college students in higher education settings requires helping professionals to more clearly understand their unique racial identity developmental needs and experiences with discrimination in order to fortify their academic endeavors and contribute to their success. A series of 3 × 2 ANOVAs and MANOVAS were conducted to examine ethnic group differences in racial identity attitudes, perceived racial discrimination and mental health outcomes in 159 African American, Black Caribbean and Latino Caribbean college students in an urban college setting in the Northeast USA. Results indicated that dissonance and immersion racial identity status attitudes were significantly linked to perceived racial discrimination and depression for all participants. Findings also showed a main interaction effect between ethnicity and racial identity conformity attitudes and mental health outcomes with high conformity linked to increased perceived stress for Latino Caribbeans and Black Caribbeans compared to African Americans. Implications for mental health practitioners and ongoing research are discussed.